Analisis Strategi Pengembangan Obyek Wisata Air Panas Cipari Kabupaten Cilacap - - Suliyanto (Conference In Business, Accounting, And Management (CBAM), 2012)
The aims of this study to analyze the feasibility of investement and to make strategy for the development of tourism destination hot water Cipari in Cilacap regency. Analysis tools to analyze feasibility of market and social economic aspec used descriptive analysis, to analyze the investment feasibility of financial aspec used Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), while the analyze tool to analyze fitness of strategy used SWOT analysis and matrix space analysis. Based on the analysis can be concluded tourism destination hot water Cipari have potencial market and positive effect on economy society, strategy to develop of tourism destination hot water Cipari was agresive.Keywords: feasibility investment, strategy, and tourism destination.